A heart revealed : a novel - Lessman, Julie, 1950- (Lessman, Julie, 1950- Winds of change, 2011)
Ten years ago, Emma Malloy fled Dublin for Boston as a battered woman, escaping the husband who scarred her beautiful face. The physical and emotional wounds have faded with time, and her life is finally full of purpose and free from the pain of her past. But when she falls for her friend Charity's handsome and charming brother, Sean O'Connor, fear and shame threaten to destroy her. Could Sean and Emma ever have a future together? Or is Emma doomed to live out the rest of her life denying the only true love she's ever known?